Formal methods and software engineering : 19th International Conference on Formal Engineering Methods, ICFEM 2017, Xi'an, China, November 13-17, 2017, Proceedings /: 19th International Conference on Formal Engineering Methods, ICFEM 2017, Xi'an, China, November 13-17, 2017, Proceedings. (2017) - Unknown
No abstract available